2023
DOI: 10.1002/eji.202350413
|View full text |Cite
|
Sign up to set email alerts
|

Bystander activation of tissue‐resident memory CD4 T cells: Getting by with a little help from unfamiliar T‐cell friends

Abstract: Reexposure to a pathogen triggers the activation of memory T cells that have already encountered a similar microbe. These long‐lived CD4 T cells either circulate through the blood and tissues or reside within organs and are referred to as tissue‐resident T cells (CD4 TRM). In the current issue of the European Journal of Immunology [Eur. J. Immunol. 2023. 53: 2250247] issue, Curham et al. found that tissue‐resident memory CD4 T cells in the lung and nasal tissues can respond to noncognate immune challenges. CD4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Since CD8 + CD103 + T RM cells do not show an increase in TCR signaling activity and seem to respond in a TCR‐independent manner after antigen reencounter, it will be interesting to determine what signals activate these cells. A recent report found that CD4 + T RM cells in the lung that formed after Bordetella pertussis infection in mice were able to respond to non‐cognate immune challenges 97,98 . These findings show that the TCR‐independent activation of T RM can occur in both CD4 + and CD8 + T RM cells and suggest that T RM might acquire innate‐like features to respond to secondary infection at barrier sites.…”
Section: Trm In Secondary Infectionsmentioning
confidence: 79%
See 1 more Smart Citation
“…Since CD8 + CD103 + T RM cells do not show an increase in TCR signaling activity and seem to respond in a TCR‐independent manner after antigen reencounter, it will be interesting to determine what signals activate these cells. A recent report found that CD4 + T RM cells in the lung that formed after Bordetella pertussis infection in mice were able to respond to non‐cognate immune challenges 97,98 . These findings show that the TCR‐independent activation of T RM can occur in both CD4 + and CD8 + T RM cells and suggest that T RM might acquire innate‐like features to respond to secondary infection at barrier sites.…”
Section: Trm In Secondary Infectionsmentioning
confidence: 79%
“…A recent report found that CD4 + T RM cells in the lung that formed after Bordetella pertussis infection in mice were able to respond to non-cognate immune challenges. 97,98 These findings show that the TCR-independent activation of T RM can occur in both CD4 + and CD8 + T RM cells and suggest that T RM might acquire innatelike features to respond to secondary infection at barrier sites. The lack of proliferative capacity of CD103 + T RM cells might be a physiological adaptation to limit immunopathology.…”
Section: T R M In S Econdary Infec Ti On Smentioning
confidence: 79%
“…Therefore, when immunity in tissue/microenvironment-control is considered and beyond the epigenetic memory mentioned above, the long-held dichotomy between innate and adaptive immune responses where primary encounter with microbial pathogens trigger the differentiation of adaptive immune cells into functional effectors that usually take several days or even longer to mature, making them contribute to host protection only late during primary infection, and, once generated, persisting these antigen-experienced T lymphocytes in the organism to constitute a pool of memory cells that mediate fast and effective protection to a recall infection with the same microbial pathogens, is no longer tenable. The "innate nature" of memory CD8 + T cells has been lately clearly demonstrated (Lauvau & Goriely 2016;Ariotti, Hogenbirk, Dijkgraaf, & others 2014;Cornelis & Shulman 2023;Cronkite & Strutt 2018) possessing effector functions that protect the host immediately against infection (Swain, McKinstry, & Strutt 2012). These effector functions are, for the most part, recalled independently of CD80, CD86, and CD40 costimulatory molecules and independent of their production of the classic proinflammatory cytokines TNF and IFN-γ (Croft, Bradley, & Swain 1994).…”
Section: Tissue/microenvironment-controlmentioning
confidence: 99%